A new species of Parandrinae from the Central Andes of Colombia (Coleoptera: Cerambycidae) - Cardona-Duque, Juliana; Santos-Silva, Antonio; Wolff, Marta (Zootaxa, 2007)
All known species of Parandra (Parandra) are distributed in Central America and the Caribbean region; a new species, Parandra (P.) antioquensis (Coleoptera: Cerambycidae: Parandrinae: Parandrini) from Colombia is here described. A key to the species of Parandra (Parandra) is presented.